Analysis of the Effect of Thermal Condition Parameters on the Strength of the Coil Lifting C-Hook Using the Finite Element Method (Case Study at PT. X) - Raja Shadam Ali Imron; Sigit Pradana; Damora Rhakasywi (Green Publisher Indonesia, 2025)
In the steel industry, Coil Lifting C-Hooks are used to lift high-temperature wire rods after rolling. The main challenge with this tool is repeated loading and high temperatures, which affect its structural strength. This study uses Finite Element Method (FEM) simulation in ANSYS to analyze the impact of repeated loading and high temperatures on structural strength parameters at temperatures of 170°C and 200°C. The simulation was conducted using steady-state thermal analysis and followed by static structural analysis. The results show that repeated loading and increased temperature increase deformation (maximum 2.4358 mm) at 170°C and (maximum 2.425 mm) at 200°C, von-Mises stress (maximum 140.86 MPa) at 170°C and (maximum 158.53 MPa) at 200°C, and reduced fatigue life (minimum 2,286,900 cycles) at 170°C and (minimum 1,394,500 cycles) at 200°C, as well as the safety factor (minimum 1.0954) at 170°C and (minimum 0.973) at 200°C, particularly in the C-Hook curved area. This underscores the importance of C-Hook design that accounts for thermal effects.